The role of HLA-DRB1 shared epitope alleles in predicting short-term response to leflunomide in rheumatoid arthritis - DİRESKENELİ, RAFİ HANER (OXFORD UNIV PRESS, 2007)
Objectives. To investigate the role of shared epitope (SE) alleles in the short-term clinical response to leflunomide for the treatment of active RA. Methods. In an open-label, multi-centre study of 16-weeks duration, 93 patients (82% female) fulfilling ARA 1987 RA criteria were treated with leflunomide (100 mg loading dose for 3 days, then 20 mg/day as the maintenance dose). The primary efficacy criterion was the response status according to the European League Against Rheumatism (EULAR) response criteria using Disease Activity Score-28 (DAS28) activity measure. SE determinations have been undertaken by polymerase chain reaction and sequencespecific oligonucleotide genotyping methods. Results. The mean (S.D) Disease Activity Score-28 (DAS28) was 5.1 (1.3) before the treatment, which was significantly decreased after 16 weeks [3.0 (1.1), P < 0.001]. According to the EULAR response criteria, 55 patients (59.1%) were classified as good responders. SE was positive in 51 (54.8) of the patients, with 13 (13.9%) having SE homozygosity or carrying any two SE alleles. Among SE-positive patients, 68.6% (35/51) were good responders, compared with 47.6% (20/42) in SE negatives (P < 0.04). No difference was present according to SE hetero- or homozygosity (68.4 vs 69.2%). RF was also present significantly more frequently in the SE-positive group compared with negatives (78.4 vs 57.1%, P = 0.03). However, no significant difference was observed in the prevalence of RF positivity in patients with a good clinical response (72.7 vs 63.2%, P = 0.32). Conclusions. The results suggest that HLA-DRB1 SE presence may favourably affect the outcome of leflunomide monotherapy in an unselected group of RA patients with an active disease and naive to leflunomide.
Keywords: leflunomide; rheumatoid arthritis; shared epitope